Effect of Adding Inhibitors from Dried Tea Leaf Powder and Calcium Nitrate to Concrete and Reinforcement on the Corrosion Rate of Reinforcement and Concrete Compressive Strength - Suhartono; Resmi Bestari Muin (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
Indonesia has many coastal areas; sometimes coastal areas have a typical problem like seawater intrusion, causing seawater to be forced to be used as a solution, replacing fresh water in concrete mixtures. However, using seawater can be harmful to the reinforcement because of the chloride ion content in seawater. The result of this study is to determine the effect of seawater on reinforced concrete, as well as examine corrosion inhibitors that can reduce the corrosion rate of concrete reinforcement, the effects of reinforcement on corrosion rate, and the effect of concrete on compressive strength when added inhibitor material. Research method using experimental by making concrete specimens using seawater as a mixing agent for concrete mortar, adding calcium nitrate to it, and in other concrete specimens adding crushed tea leaves. Concrete bar using a plain round reinforcing bar with a diameter of 10 mm and 280 MPa tensile strength. The results of the analysis showed that concrete with a mixture of tea leaves weighing 1.6 kg/m3 of concrete produced the smallest iron weight loss; the largest compressive strength for concrete with inhibitor was produced by concrete specimens with tea leaves weighing 0.8 kg/m3 of concrete.